한국 노인의 인구·사회경제적 특성과 미 충족 치과진료와의 관련성 - 정은서; Eun-seo Jung; 안금선; Geum-sun Ahn (Han'guk Ch'iwisaeng Hakhoe chi, 2018)
Objectives: This study investigated the relationship between demographic and socioeconomic characteristics of the Korean elderly and their unmet dental care needs, by using the 2015 data from the 6th Korea National Health and Nutrition Examination Survey (NHANES). Methods: In total, 1,372 elderly persons aged 65 and over, who responded to the 6th NHANES, were included in the final analysis. Logistic regression analysis was performed in order to identify any relationship between demographic and socioeconomic characteristics and unmet dental care needs. Results: The rate of unmet dental care needs was shown to be less by 0.799 times in the elderly who reside in dong than those who live in eup and myeon (OR: 0.799, 95% CI: 0.679-0.959). Unmet dental care needs were higher in participants with ‘low’ and ‘below average’ than ‘above average’ income, by 1.645 times (OR: 1.645, 95% CI: 1.087-2.366) and 1.172 times (OR: 1.172, 95% CI: 1.108-1.880), respectively. Elderly individuals living alone had a higher rate of unmet dental care needs than those living with their family by 1.157 times (OR: 1.157, 95% CI: 1.084-1.498). Conclusions: Demographic and socioeconomic factors influenced unmet dental care needs, causing inequality. Proper policy support to the vulnerable should be considered in order to enhance the elderly’s access to dental care.